Zoonosis : Infeksi penyakit ikan terhadap manusia akibat kesalahan manajemen dan penanganan ikan maupun produk olahannya - Boby Dani Darmawan; Otong Endi Rohaendi (Jurusan Akuakultur, Universitas Bangka Belitung, 2014)
Fish pathogens cause disease in many species of freshwater and marine fish; however, relatively few fish pathogens were known to be zoonotic or causing disease in humans. Zoonotic disease transmission from animals primarily through direct contact, direct contact with vectors and contaminated media, oral ingestion or inhalation of aerosols. Several bacterial pathogens among the potential zoonotic can be found in association with aquatic animals. Aquatic animals live in a wide range of conditions, thereby in fuencing the particular bacterial species that are associated with certain species. Aeromonas spp.; for example, is more commonly associated with freshwater species, whereas Vibrio spp. is generally associated with marine species of aquatic organisms. The most important of the helminths acquired by human from fish were herring worms (Anisakis species) or cod worms (Pseudoterranova decipiens), Diphyllobothrium latum, Paragonimus westermani, liver fluke (Clonorchis sinensis and Opistorchis viverrini), intestinal worms (family Heterophyidae and family Echinostomatidae), Angiostrongylus cantonensis, Spirometra erinacei-europaei (tapeworm) and Gnathostoma spp. (nematodes). All of the parasites mentioned above were associated with social-cultural and behavioural factors, in particular the consumption of raw or undercooked seafood, while the risk to human of contracting infection from fish pathogens was generally low. There were some cases of zoonoses that cause fatal consequences, such as paralysis or even death. Awareness against potential risks is important for fishery managers, anglers, and commercial fishermen.